2019
DOI: 10.3389/fmicb.2018.03116
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Related Features and Virulence Among Acinetobacter baumannii Clinical Isolates Belonging to International Clones I and II

Abstract: Acinetobacter baumannii currently represents one of the most important nosocomial infection agent due to its multidrug-resistance and a propensity for the epidemic spread. The A. baumannii strains belonging to the international clonal lineages I (IC I) and II (IC II) are associated with the hospital outbreaks and a high virulence. However, the intra and inter lineage-specific features of strains belonging to these most worldwide spread A. baumannii clones are not thoroughly explored. In this study we have inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 63 publications
9
55
0
Order By: Relevance
“…These results suggest that Wza affects the formation of bacterial capsules. Russo et al constructed the wza mutant and found that the wza mutants were capsule deficient [18], Skerniškytė J et al also constructed a wza mutant and found it was a CPSnegative phenotype [26]. These studies were consistent with the results of the cell wall we assessed by TEM.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results suggest that Wza affects the formation of bacterial capsules. Russo et al constructed the wza mutant and found that the wza mutants were capsule deficient [18], Skerniškytė J et al also constructed a wza mutant and found it was a CPSnegative phenotype [26]. These studies were consistent with the results of the cell wall we assessed by TEM.…”
Section: Discussionsupporting
confidence: 79%
“…Based on the bacterial toxicity test results of our study, Russo et al 2010 [18] and Skerniskyte et al 2019 [26], we found that after wza knockout, bacteria couldn't form capsule layer, which was easily killed by the immune system of the host, and what effect does wza have on the wzy pathway? whether the absence of Wza affects the expression of other molecules involved in the synthesis of Wzy capsular polysaccharides has not been reported.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In A. baumannii, hydrophobicity has previously been correlated with increased adherence to abiotic surfaces but not to buccal epithelial cells (Costa et al, 2006;Pour et al, 2011). Furthermore, a recent study analyzed 16 clinical isolates of A. baumannii in the International Clone Lineage II (IC-II) and found the more hydrophobic strains produced increased biofilms, adhered more readily to abiotic surfaces, and had decreased virulence compared to the more hydrophilic isolates (Skerniskyte et al, 2018). Our laboratory has recently suggested the previously unidentified role of thioredoxin in surface hydrophobicity of an A. baumannii clinical isolate Ci79 (May et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ci79 was genome sequenced (Ketter et al, 2014a), and largescale whole genome phylogenic analysis indicates a closer genetic relationship with AYE (IC-I) and ATCC strains 19606, 17978 than ACICU strain (IC-II). Twitching motility and pellicle formation are strongly associated with IC-I lineage strains (Eijkelkamp et al, 2011;Skerniskyte et al, 2018). Deletion of the thioredoxin A gene in Ci79 (ΔtrxA) greatly reduced twitching motility and surface type IV pili (T4P), but increased biofilm formation and cell surface hydrophobicity (CSH) as measured by Congo Red binding (May et al, 2019).…”
Section: Introductionmentioning
confidence: 99%